PHILOSOPHY LAW ISLAM (TASYR'I) - Abdul Mannang; Achmad Musyahid; Rahmatiah (Multidisciplinary Indonesian Center Journal (MICJO), 2025)
Philosophy law Islam or tasyr'i is runway philosophical Which underlying all over building law Islam, Which regulates human relations with God and fellow human beings in everyday life. Through the study of Islamic legal philosophy, we can understand the goals, basis, and principles underlying the application of law in the lives of Muslims. This study aims to examine the essence of Islamic legal philosophy by identifying its sources of law, the values contained, as well as objective Which want to achieved. Method study This is studies literature with approach descriptive-analytical to understand the concepts of Islamic legal philosophy. This analysis describes the concept of tasyr'i as a way to maintain human welfare and prevent damage. The results of this study indicate that tasyr'i is not only formal legal but also functions as a moral, social, and spiritual guide to achieve justice and human welfare.